Clinical outcome of tubercular pleural effusion in patients treated under revised national tuberculosis control programme - M. R., Lokesh; M. G., Bhutto; H., Chaithra (International Journal of Advances in Medicine, 2016)
Background: Although it is curable, tuberculosis remains one of the most frequent causes of pleural effusions on a global scale, especially in developing countries. Tuberculous pleural effusion (TPE) is one of the most common forms of extrapulmonary tuberculosis. The recommended treatment for TPE was regimen developed by revised national tuberculosis control programme- directly observed treatment-short course (RNTCP-DOTS). Methods: The present study was conducted at Sri Siddhartha medical college hospital and research centre, Tumkur (Tumakuru), Karnataka, India for one and half year during the period of October 2010 to April 2012. 50 patients were included in the study after meeting inclusion criteria. Detailed history and clinical examination of patients were done including chest X-ray. Treatment was given with RNTCP-DOTS regimen. After complete treatment the recovery of patients was evaluated by chest X-ray. Results: A total of 50 patients were included in the study. The mean age group was 41 years. Male (62%) preponderance was seen compared to females (38%). Chest pain and fever are the common clinical symptoms observed in all the patients. Moderate amount of pleural fluid accumulation was seen in 41 (82%) cases. Presence of lymphocytes was noted in all the samples. Out of 50 patients, 4 (8%) of them are detected as HIV positive and 6 (12%) are noticed as diabetic. 48 (96%) patients were having pleural fluid protein value more than 2.9 g/dl and 49 (98%) patients had pleural fluid sugar more than 60 mg/dl. 14 (43%) were reported of having ADA (elaborate the abbreviation- Adenosine deaminase) in the ranges 100-150 U/L. 30 (60%) patients were reported of having >10 g/dl of hemoglobin, 36 (72%) with total leucocyte count 4000-11000 cells/cumm and 45 (90%) with ESR >20 mm/hr. After completion of treatment out of 50, 40 patients were analyzed with chest X-ray and the outcome observed was normal appearance. Conclusions: Early detection of tuberculosis was done by pleural fluid analysis and chest X-ray. After complete treatment with RNTCP-DOTS regimen all TPE cases produced significant cure rate when examined by chest X-ray.